Growth, physiological and biochemical responses of Malaysia rice cultivars to water stress - Baharudin, Wan Mohammad Zukarnain; Ismail, Mohd Razi; Md Ashrafuzzaman; Mohd Saud, Halimi; Haroun, Ismail C. (Universiti Putra Malaysia Press, 2009)
The response of water deficit on rice plants varies substantially according to cultivars. Drought tolerant cultivars possess better morphological, physiological and biochemical adaptation to reduce water availability. An experiment involving water stress on rice varieties was carried out under rain shelter to examine the morphological changes (leaf rolling, root depth), stomatal responses and biochemical processes (proline and peroxidase accumulation) of five different local rice varieties. These varieties were selected based on their drought tolerant potential from an earlier varietal screening trial. The varieties were taken from both traditional (Muda, Jawi Lanjut and newly breed commercial varieties, MR 84, MR219 and MR 220) obtained from Genebank, MARDI Research Station, Seberang Prai, Kepala Batas, Pulau Pinang. These varieties were exposed to two different water regimes; water stress by withholding water and well watered condition (control). The experiment was carried out in a Complete Randomized Design (CRD) with 4 replicates. Water stress plants exhibited lower growth rate with obvious variation among rice varieties on the sensitivity to water stress. Meanwhile, the overall sensitivity of the varieties to water stress was ranked in the order; MR220>Muda>MR84>MR219>Jawi Lanjut. Water deficit decreased stomatal conductance, relative water content and root depth while peroxidase activities and proline accumulation were increased in rice grown under water stress treatment.